INDONESIAN TERTIARY SEDIMENTARY BASIN - Djoko Sunarjanto; Sri Wijaya; Suprajitno Munadi; Bambang Wiyanto; Doma F. Prasetio (Scientific Contributions Oil and Gas, 2008)
Since 1980 the number of Indonesian Sedimentary Basin which is officially announced by the government are 60 basins, but informally the variation in the range of less than 60 up to around 66 basins. Based on stratigraphic and tectonics conditions of some areas there are overlapping layers between Tertiary Sedimentary and Pre Tertiary Basin. In general the definition of a sedimentary basin is a region, part of the earth's crust where sedimentary strata have been deposited in a relatively much greater thickness than its surrounding area. The nomenclature for basin is referred more to basinal areas. Based on sedimentary basin classification there are: type of plate where basin exists, basin position in the plate margin, type of plate interaction, time development of basin and basins fill with respect to tectonic and shape of the basin. The updating classification using new technology and knowledge of the basin, can also update previous knowledge because of the limitation of the data and the lack of new concept when the report was published. 63 Tertiary Sedimentary Basins (16 producing basin of oil and gas, 8 drilled basin with discovery, 15 drilled basin with has no discovery yet and 24 basin which has not been drilled yet) could be used as a basic data for development of science and technology, to support government policy and investor, to improve and accelerate oil and gas exploration and production in Indonesia.